Integrative Analytics for Technological Pedagogical Content Knowledge. (27th November 2021) - Zhang, Jin-E.
Abstract : In this paper, we deeply analyze the general framework of technological pedagogical content knowledge (TPACK): it mainly involves technological knowledge (TK), pedagogical knowledge (PK), content knowledge (CK), technological content knowledge (TCK), technological pedagogical knowledge (TPK), and pedagogical content knowledge (PCK). Meanwhile, we also show that the conceptual framework of TPACK can help teachers to integrate a lot of complexity and tension in teaching and learning. Also, this study suggests that the framework of TPACK may be able to change the application mode of technology in education and the training mode of teachers and then provide a panoramic analysis for building a learning community.